Modifikasi Penambahan Line Emergency Back Up GSW Head Tank Pada PLTU Suralaya Unit 1-4 - Jasmid Edy; Mu’ridin Mu’ridin (JURNAL POWERPLANT, 2015)
Cooling System teaching aids or GSW (General Service Water) is used for cooling system equipment lubrication aids Suralaya Power Plant in the water use demin (pure water) as its media. Issues that frequently occurred in unit is terkontaminasinya water demin by emergency back up GSW Head tank of water fire fighting that have chemical composition water that is different from water demin. This is because emergency back up normal (by pass valve) from demin supply pump could not be fully back up level low GSW Head tanks that can cause unit Trip if level was not immediately dinormalkan. If this is allowed to be continuously and not anticipated so it can cause corrosion, deposit and water pipes porous in line cooling assist (GSW which became a loss for the company financially cooling process equipment and helping to not optimal. One of offered solutions is to replace emergency supplies back up GSW Head tanks from fire fighting by using supplies from RFW (Reserve are Sent Electronically Water tanks which both of the same using the media water demin so terkontaminasinya water GSW can be minimized.